MEMAHAMI HADITS NABI SECARA INTERTEKSTUAL - Masyhuri Rifai; Andika Andika (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The subject of this study discusses how to understand the hadith of the Prophet Muhammad. Not based on just one text but rather comparing one text with another text, can be obtained from hadith texts and from the quran. This is called intertextual understanding. The main object is the hadith of the Prophet Muhammad. With intertextual understanding, the method used is 1) gathering hadith into the same theme. 2) Connection or commentary between Hadiths (Apparently) Contradictory. The approach used is the socio-historical approach. this approach is used to examine the truth of the hadith and analyze the history of the hadith so that the meanings contained in each hadith of the Prophet are known. The results conclude that there are two examples of understanding the prophetic traditions based on intertextuals, namely 1) the most important charity, which after being collected with the same hadiths can be concluded that the most important charities are various. it can also be understood that for the same questions (similar), it turns out that the answer can be different. Thus, the Prophet's answer to the same questions (similar) is temporal, precisely conditional. And not universal. 2) isbal, if it is reconciled with the same hadith, it is concluded that isbal is fine as long as it is not accompanied by arrogance. Besides that, sometimes there are hadiths if they are found to be contradictory as the apostle's wc problem turns to face the Qiblah, whereas in other traditions it is prohibited from facing the Qibla. After the meeting was found a solution that